PENGARUH METODE PAIRED STORY TELLING TERHADAP KETERAMPILAN BERBICARA SISWA KELAS IV SDN GUGUS 8 KECAMATAN JANAPRIA - Sasy Ahadatul Alawiyah; Husniati Husniati; Heri Setiawan (Renjana Pendidikan Dasar, 2021)
The purpose of this research is to understand the influence of using Paired Story Telling method toward the speaking skill of fourth grade students at SDN Gugus 8 in Subdistrict Janapria academic year of 2020/2021. This research is experimental research. Samples of this research are including 16 fourth grade students of SDN 2 Bakan and 16 fourth grade students of SDN 1 Selebung. The method of collecting data in this research are using observation and performance test to the sample students. Speaking skill datas are collected by the speaking skill assessment rubric. All of the collected data then analyzed with inferential statistic (T-test) that should pass some prerequisite tests, such as normality test and homogeneity test. Based on the prerequisite tests, all of the data stated as normal and have homogeneity variant. Furthermore to verify the hypothesis by using the Independent Sample T-test that indicate the sig`2 tailed speaking skill value in the amount of 0.046 less than 0.05 (0.046 ˂ 0.05). This showed that the alternative hypothesis (Ha) is accepted and zero hypothesis (H0) is rejected. The conclusion of this research is to indicate the positive and siginificant influence of Paired Story Telling method to improve student’s speaking skill, especially fourth grade students at SDN 1 Selebung and SDN 2 Bakan in Subdistrict Janapria academic year of 2020/2021, so that in the future this method could be use by the teacher to improve student’s speaking skill.